The peculiarities of practical use of ordinal and cardinal numerals in modern English - Griceshena, L.; Kylyvnik, V. V.; Грицишена, Л.; Киливник, В. В. (Вінницька міська друкарня, 2022)
The author of the article represents the peculiarities of practical use of ordinal and cardinal numerals in modern English. For example the author shows use of ordinal numbers in literature and the use of cardinal numerals in modern English idioms and proverbs.
Особливості практичного використання порядкових та кількісних числівників у сучасній англійській мові
Keywords: amount; cardinal; number; order; ordinal; quantity; numeral